รัฐศาสตร์แนวพุทธ: ว่าด้วยแก่นจริยธรรมการปกครองไทย - จินดารัมย์, ณัฐพล; โสภาจร, วัชรพงษ์; วันคำ, วิพจน์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 1 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 1 : มกราคม - เมษายน 2567, 2024)
The Thai nation, both in prehistoric and historical times, has long had a way of life intertwined with Buddhism. Regarding governance, the Thai people have utilized Buddhist teachings to such an extent that they have become deeply ingrained in their minds. Consequently, the core ethics of Thai governance consistently revolve around the principles of "Sila" (moral conduct), which are human laws, and "Dhamma" (natural laws), both of which are guidelines that must be practiced together. When explaining various teachings in terms of ethical governance, as understood globally and discussed in contemporary Thai society, the analysis of Buddhist teachings reveals core ethical principles concerning liberty (the right to act), equality (the duty to act), and fraternity (the obligation to act as brothers and sisters). In essence, everyone has the freedom to act, must act equally, and should act with a sense of brotherhood. These three principles must be practiced together in unity.